2018
DOI: 10.1093/ptj/pzy018
|View full text |Cite
|
Sign up to set email alerts
|

Delivering Intensive Rehabilitation in Stroke: Factors Influencing Implementation

Abstract: Even therapists involved in delivering a high-intensity intervention as part of a trial wanted to adapt it for clinical practice; therefore, it is imperative that researchers are explicit regarding key intervention components and what can be adapted to help ensure implementation fidelity. Changes in therapists' beliefs and system-level changes (staffing and resources) are likely necessary to facilitate higher-intensity rehabilitation in practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 32 publications
0
36
0
Order By: Relevance
“…The study characteristics for the 22 included studies are presented in Table 1. The studies originated from seven different countries: nine from Australia, 2127 seven from Canada, 2834 two from the United Kingdom, 35,36 one from Norway 37 one from Ireland, 38 one from New Zealand 39 and one from the Netherlands. 40 There was a total of 850 included participants comprised of 371 speech language pathologists, 356 physiotherapists, 100 occupational therapists, four dieticians, five rehabilitation assistants/therapy assistants, two social workers and one psychologist.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The study characteristics for the 22 included studies are presented in Table 1. The studies originated from seven different countries: nine from Australia, 2127 seven from Canada, 2834 two from the United Kingdom, 35,36 one from Norway 37 one from Ireland, 38 one from New Zealand 39 and one from the Netherlands. 40 There was a total of 850 included participants comprised of 371 speech language pathologists, 356 physiotherapists, 100 occupational therapists, four dieticians, five rehabilitation assistants/therapy assistants, two social workers and one psychologist.…”
Section: Resultsmentioning
confidence: 99%
“…The appraisal findings were limited to what was reported in the studies. Only eight studies reported that sampling occurred until data saturation was reached 22,3033,37,40,41 and five needed to provide more information about the locations for data collection. 3032,39,40 Explanation of the role of researchers and their biases and assumptions were missing in seven studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One avenue to target walking for individuals with stroke may be to utilize wearable monitoring technology, as previous research has shown that application of an activity monitor can improve user self-efficacy and physical activity levels in various patient populations including older adults, breast cancer survivors, and those with chronic obstructive pulmonary disease [7][8][9][10][11]. Additionally, wearable monitors have been increasingly utilized by therapists and researchers to assess various outcomes relating to exercise and physical activity, [12,13] within therapy and between visits, to ensure exercise targets are met [14].…”
Section: Introductionmentioning
confidence: 99%